Antecedents and Consequences of Unawareness of Memory Impairment in Dementia - Wilson, Robert S. (Neuropsychology, 2018)
OBJECTIVE: To assess the prevalence, antecedents, and consequences of unawareness of memory impairment in dementia. METHODS: Persons (n=1,862) from a geographically defined community without dementia at enrollment subsequently underwent clinical classification (248 with dementia, 611 with mild cognitive impairment, 1,003 with no cognitive impairment), memory testing, and self-appraisal of memory. Memory performance was regressed on self-appraised memory, and the residuals served as an index of memory awareness. After clinical classification, participants completed brief cognitive testing at three-year intervals for up to 15 years. RESULTS: When unawareness was defined as a score at or below thresholds ranging from the 15(th) to 25(th) percentiles, it was more common in dementia (67% - 83%) and mild cognitive impairment (15% - 33%) than in no cognitive impairment (2% - 6%; all p<0.001). A continuous measure of awareness (mean=0.00, SD=0.61) was reduced by 0.37-unit in mild cognitive impairment (SE=0.04, p<0.001) and 1.04-unit in dementia (SE=0.06), p<0.001) compared to those without cognitive impairment, and these associations were weaker in Black persons than White persons (estimate for dementia by race=0.37, SE=0.12, p=0.003; estimate for mild cognitive impairment by race = 0.30, SE=0.08, p<0.001). Higher premorbid neuroticism was associated with better memory awareness in dementia. Higher memory awareness was not related to mortality in mild cognitive impairment or dementia but had a marginal association with slower cognitive decline in mild cognitive impairment. CONCLUSIONS: Unawareness of memory impairment is a common manifestation of dementia, particularly in White persons, but is not strongly related to adverse disease outcomes.